2021
DOI: 10.2174/1566524020666200220141414
|View full text |Cite
|
Sign up to set email alerts
|

High Plasmatic Levels of Advanced Glycation End Products are Associated with Metabolic Alterations and Insulin Resistance in Preeclamptic Women

Abstract: Aims: The purpose of this study was to investigate the association between plasmatic levels of advanced end glycation products (AGEs) and the metabolic profile in subjects diagnosed with preeclampsia, due to the known relation of these molecules with oxidative stress and inflammation, which in turn are related with PE pathogenesis. Background: It has been reported that increased levels of AGEs are observed in patients with preeclampsia as compared with healthy pregnant subjects, which was mainly associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Little is known about the levels of circulating AGEs in pregnancy. One study found elevated serum AGE levels in women with PE [17], while another suggested that gestational diabetes was associated with increased serum AGE levels [18]. Single studies indicate the potential applicability of protein glycation end products in predicting premature rupture of the amniotic fluid sac and preterm labor [19].…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the levels of circulating AGEs in pregnancy. One study found elevated serum AGE levels in women with PE [17], while another suggested that gestational diabetes was associated with increased serum AGE levels [18]. Single studies indicate the potential applicability of protein glycation end products in predicting premature rupture of the amniotic fluid sac and preterm labor [19].…”
Section: Discussionmentioning
confidence: 99%
“…Mid-trimester maternal IR is associated with later PE [11]. Hepatic and metabolic profiles, especially those associated with IR, are higher in PE than in healthy pregnant women [12]. One of the less studied pathways in the PE is the kynurenine pathway (KP), which degrades 95% of the tryptophan (TRP) to kynurenine (KYN) and either its neurotoxic or neuroprotective immunogenic metabolites [13].…”
Section: Introductionmentioning
confidence: 99%